Interdisciplinary collaboration in management of nutrition during chemoradiotherapy in cancer patients: A pilot study [Kanser hastalarında kemoradyoterapi sırasında beslenme yönetiminde disiplinler arası i̇şbirliǧinin yeri: Bir pilot çalışma] - (:unkn) unknown (Marmara University, 2012)
Objective: To assess the effectiveness of close and intense monitoring on nutritional status of cancer patients involving a dietitian and a nutrition education nurse during chemoradiotherapy (CRT). Patients and Methods: Fourteen curative CRT patients diagnosed with head and neck (n=10), gastrointestinal system (n=3) or lung (n=1) cancer were recruited into this prospective study. A subjective global assessment (SGA) scale was used for nutritional assessment at the beginning and in every week of CRT. Weekly follow-ups were done in hospital by the dietitian and at home by the nutrition nurse. Beside the nutritional parameters home visits included care givers assessment for their response to recommendations. Results: Three patients had mild malnutrition (SGA-B) at the beginning of CRT. However, 8 patients had SGA-B and one SGA-C (severe malnutrition) at the end of CRT. The response of the care givers to nutritional recommendations was adequate to excellent. All newly diagnosed malnourished patients had head and neck tumors and either refused supportive care (n=2) or were older than 80 years (n=2) or had a low performance status (n=1). Conclusion: Despite an adequate support and follow-up, nutritional parameters may deteriorate in older age, and in low performance head and neck cancer patients during CRT. Defining the risk factors initially may help to determine the level of nutritional support. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Cancer; Chemoradiotherapy; Nursing; Nutritional support